Protective Effects of Aqueous Extract of Allium Sativum (Garlic) On the Histomorphology and Biochemical Parameters of Lead -Induced Cerebellar Injury on the Adult Male Wistar Rats - Agu, Augustine U; Chime, Samuel C; Duru, Kelechi; Abah, Stephanie I; Ogonnadi, Kpokuechukwu C; Ugwu, Augustus U (International Journal of Membrane Science and Technology, 2023)
The study was aimed at evaluating the effects of an aqueous extract of Allium sativum on the biochemical parameters and histo-architecture of lead-induced cerebella damage in male Wistar rats. Sixteen male rats were procured for the study. They were divided into 4 groups, with 4 rats in each group. Group 1 (Control group) received only food and water, those in group 2 were given lead at the dosage of 120 mg/kg body weight. Group 3 received lead at the dosage of 120 mg/kg body weight and the extract at 300 mg/kg body weight while those in group 4 were given lead at the dosage of 120 mg/kg and 500 mg/kg body weight of the extract. The extracts were administered orally for 21 days. Blood samples were collected for biochemical evaluation. The rats were sacrificed, and their cerebella were harvested for histo-morphological studies. The levels of Superoxide dismutase (22.49 ± 1.21) and Malondialdehyde (1.17 ± 0.092) were normal in group 1. There was significant derangement in their levels in group 2, Superoxide dismutase (9.83 ± 0.93) and Malondialdehyde (11.42 ± 1.82). In groups 3 and 4, the levels of Superoxide dismutase increased towards the levels of the control group (12.81 ± 1.13, 16.06 ± 0.29), while those of Malondialdehyde also decreased towards the levels of the control group (6.49 ± 0.57, 3.12 ± 0.36). The histo-architecture of the cerebella in group 1, appeared normal, those in group 2 showed traumatic encephalopathy of the granular cell layer. In groups 3 and 4, there was mild tissue traumatic encephalopathy. The extract of A. sativum showed a significant protective effect on the biochemical parameters and histo-architecture of lead-induced cerebella damage in adult male Wistar rats.